Unveiling the Digital Literacy Landscape: A Decade of Insights from a Scopus Bibliometric Analysis (2013-2023) - Andhim, Muk.; Maksum, Muh. Nur Rochim; Maharani, Andi Rezti; Ridwan, Mohammad; Sriyono, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The aim of this research is to describe the direction map and development of digital literacy research in articles indexed by Scopus. This research examines all digital literacy publications indexed in the Scopus database between 2013 and 2023 using an analytical bibliometric approach. Utilizing R/R-Studio and Excel in processing data. Visual analysis of the occurrence of document quotes and keywords was carried out with VOSviewer. The specified function, subject, and criteria were met by 1,161 publications found. Based on the study's findings, the largest peak in digital literacy publications will occur in 2023, with a growth rate of 22% each year. The country that contributed the most publications was the United States. The University of Oslo is its largest affiliate. McGrew, S is the most productive writer on the theme of digital literacy. The bibliometric analysis carried out was limited to Scopus data. Other national and international databases were not taken into account in this study. This research presents a brief overview of the literature that can be accessed by researchers working in the field of educational innovation and technology and provides recommendations for future research.